Placental abruption an obstetric emergency: management and outcomes in 180 cases - Devabhaktuni, Pratibha; Konkathi, Aruna Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: During a period of eight months, 180 cases of abruption that occurred from January 2007 to August 2007 at GMH, Nayapool, Hyderabad were analysed. Total number of deliveries during the study period of eight months were 14004. Incidence of abruption cases delivered was - 1.3%. In this series 88% were unbooked in our hospital, were referrals. Objective of this study was to study maternal fetal outcome of placental abruption. Methods: Initial clinical assessment, investigations for maternal fetal wellbeing, expedite delivery, manage complications as per accepted protocol. In this series of cases, ARM was done in 85 cases (47.22%), ARM was done and oxytocin drip was started in 36 (20%), ARM was done and PGE1 tablet 25 mcg. was inserted in the vagina in 39 (21.66%). Results: The bleeding was revealed in 146-81.1% and concealed in 34-18.88%. The number of cases with hypertension complicating pregnancy were 102-57%, hypotension in 16-8.88%, prolonged clotting time 13-7.22%, the number of patients who received blood transfusions were 105 (58.3%), number of patients who received fresh frozen plasma, FFP transfusions were 65-36.11%. Taken for LSCS at admission were - 46. Failure to progress after ARM or other methods of labour augmentation were 20 cases. The total number of caesarean deliveries were 66/180 - (36.66%), number of vaginal deliveries were 114 (63.33%). Perinatal outcome: the total number of intra uterine fetal deaths (IUFD) at admission were 103-57.2%. The number of still births were 7-3.8%. Live born babies were 70- 38.8%. Neonatal deaths were 11-6.1% and total perinatal deaths were 121-67.2%. (IUFD at admission-103, + still births - 7, + neonatal deaths - 11=121 perinatal deaths. There were five maternal deaths in 180 cases of placental abruption, 2.7% mortality. Conclusions: Need to consider measures to reduce the occurrence of this condition.